Gender Roles in Crop and Animal Husbandry Practices and Household Activities with Respect to Changing Climate in Arid Ecosystem - Rajesh Bishnoi , Premlata Singh , S. K. Dubey; V. Sangeetha (Indian Journal of Extension Education, 2014)
Women in rural India play a major role in shaping country’s economy. The study focussed on the different roles of women and men in order to understand what they do in crop husbandry practices n animal husbandry practices as well as in routine household activities. The study was conducted in arid ecosystem of Bikaner district of Rajasthan. Two stage stratified random sampling procedure was followed selection of respondents. Total sample size was 120 comprising of 60 men and 60 women farmers. This study used gender analysis to document and interpret how men and women farmers ensured their livelihood and food security. The findings revealed that in crop husbandry activities, women were doing mainly field work like harvesting; intercultural operations and these activities are affected by climate change. Hence, their work load and drudgery needs to be addressed. Women farmers role in economic activities like selling of crop produce, selling of livestock produce etc. were considerably less compared to men farmers in crop and animal husbandry practices. Majority of the work in animal husbandry activities and routine household activities were done by the women farmers as compared to men farmers. Closing the gender gap is not only the right thing to do, it is crucial for agricultural development and food security